Eaton's reagent is an alternative of PPA: Solvent free synthesis, molecular docking and ADME studies of new angular and linear carbazole based naphtho naphthyridines. (6th April 2023) - Prabha, Kolandaivel; Satheeshkumar, Rajendran; Aathi, Muthu Sankar; Chandrasekar, Chinnarasu; Sukantha, Tiruchengode Arumugam; Gnanamangai, Balasubramanian Mythili; Acevedo, Roberto; Sayin, Koray; Prasad, Karnam Jayarampillai Rajendra
Abstract: An approach towards the preparation of novel angular and linear carbazole based naphtho naphthyridines are described in good yields. From schematic study on the condensation of 4-chloro-2-methylbenzo[ h ]quinoline and 3-amino-9-ethylcarbazole in presence of CuI as catalyst to N -(9-ethyl-9 H -carbazol-3-yl)-2-methylbenzo[ h ]quinolin-4-amine was stated as starting synthon. Thus, this carbazole based quinoline amine on treatment with Eaton's reagent catalyzed cyclisation reaction with Aromatic carboxylic acids to yield the linear and angular 8-substituted naphtho[ h ]carbazol [1, 6]naphthyridines. This Eaton's reagent is a precise catalyst for the reaction of cyclizing cum aromatization agent followed by dehydration of the conversion of angular and linear naphthyridines in excellent yields compared with Polyphosphoric acid (PPA). Further, the molecular docking studies were conducted to offer binding mode into the binding sites of phosphoinositide-dependent protein kinase 1 (PDK-1) receptors. The synthesized compounds showed better docking scores and binding energies, when compared with reference drugs ARC-111 and Ellipticine. Pharmacokinetic (ADME) parameters of the potent derivatives have also been found to an acceptable range. Graphical abstract: Graphical abstract. Image 1 Highlights: The preparation of novel angular and linear carbazole based naphthonaphthyridines through 4-chloro-2-methylbenzo[ h ]quinoline and 3-amino-9-ethylcarbazole intermediate. 4-chloro-2-methylbenzo[ h ]quinoline and 3-amino-9-ethylcarbazole was utilized for the preparation of novel angular and linear carbazole based naphthonaphthyridines. The Eaton's reagent is a precise catalyst for the preparation of angular and linear naphthyridines in excellent yields compared with Polyphosphoric acid (PPA). The molecular docking studies were conducted with phosphoinositide-dependent protein kinase 1 (PDK-1) receptors. Pharmacokinetic (ADME) parameters of the potent polycyclic analogues.